Factors associated with vitamin D deficiency in a multicultural inflammatory bowel disease cohort. Issue 1 (30th October 2012) - Chatu, Sukhdev; Chhaya, Vivek; Holmes, Rosamund; Neild, Penny; Kang, Jin-Yong; Pollok, Richard C; Poullis, Andrew
Abstract : Objective: The aim of this study was to determine the prevalence of vitamin D deficiency in a multicultural inflammatory bowel disease (IBD) cohort and determine predictors of deficiency including ethnicity. Design: Patients with IBD were recruited into a dedicated database over a 6-month period and evaluated retrospectively. Setting: Department of Gastroenterology, St George's University Hospital, London, UK. Outcomes measured: Clinical data including demographics, ethnic group, disease phenotype by the Montreal classification, vitamin D level and season tested were recorded from clinical and electronic medical records. Vitamin D levels were classified as normal (≥50 nmol/l) and deficient (<50 nmol/l). Results: 168 patients had a vitamin D level measured subsequent to diagnosis. There was no significant difference in the median vitamin D level between patients with Crohn's disease (CD) and ulcerative colitis (UC) (39 nmol/l (IQR 23–56) vs 28 nmol/l (IQR 17–51), p=0.35). Overall the median vitamin D level was significantly lower in non-Caucasians (Asian and Black) versus Caucasians (28 nmol/l (IQR 17–41) vs 41 nmol/l (IQR 25–63), p<0.0001). Multiple regression analysis revealed IBD related surgery (OR 2.9) and ethnicity (OR 6.0 non-Caucasian vs Caucasian) in CD and ethnicity (OR 5.0 non-Caucasian vs Caucasian) in UC were independently associated with vitamin D deficiency. Conclusions: Vitamin D deficiency is common in IBD patients; therefore, we suggest monitoring of vitamin D levels and correction with supplements especially in non-Caucasians and those with a history of IBD related surgery.